Gli studi francescani: percorsi storici e riflessione storiografica: tra frate Francesco e frate Antonio - Bertazzo, Luciano (Miscellanea francescana, 2020)
This contribution analyses the Franciscan and Anthonian historical path from the Sabatierian "Franciscan question" surpassed further by contributions that, in the meantime, have come to light thanks to the "rediscovery" of the Writings of St. Francis, indicating the current circumstances in relation to studies. The reflection on the Anthonian historiography that has emerged strongly in recent decades, through the importance of its Franciscan aspect, is more linear. The places and networks where these studies are vividly present are also indicated